Love in a time of hate : art and passion in the shadow of war - Illies, Florian, 1971- (Riverhead Books, 2023)
"A brilliantly constructed popular history of the world careening toward the Second World War, as told through the love lives of some of the most famous and fascinating figures of the era. As the Roaring Twenties wind down, the great minds of the time have their minds on other concerns besides art and war. Jean-Paul Sartre waits anxiously in a Parisian café for his first date with Simone de Beauvoir, who stands him up. Marlene Dietrich slips from a loveless marriage into the dive bars of Berlin. Thomas and Klaus Mann clash over the father's repressed homosexuality, the son's open embrace of his own. The fledgling writer Vladimir Nabokov places a freshly netted butterfly at the end of Vera's bed. Little do they know, the book-burning will soon begin, and they, along with millions of others, will be forced to contemplate flight--or fight--in the face of impending doom. In this ingeniously orchestrated chronicle, cultural historian Florian Illies brings to life the most pivotal decade of the century through the romantic and erotic lives of some of its most influential figures--artists and actors and activists and thinkers. As they bed, wed, betray, and fall in love, their personal dramas parallel political and cultural tensions approaching the breaking point, and the shadow of global war eclipses them all"--